Strategi Memenangkan Persaingan Dalam Menjual Cat Tembok : Studi Volume Penjualan Penjualan Pada CV. XYZ - Sujana, Sujana; Susanto, Susanto (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
Increasing market demand potential to a product and the fact that just few firms makes use of such market, itâs required accurate marketing strategy in marketing products. Based on SWOT and position of competition analysis, a firm can determine how to expand market potential, how to build product image, and how to broaden distribution network, developing of production, and developing of human resources quality